Researches on Finance and Economic Growth in Algeria "2011-2016": Critical Study - Kara, Rabah; Aldjia-Souad, Kara (جامعة ابن خلدون تيارت - الملحقة الجامعية قصر الشلالة, 2022)
This article offers a critical analysis of several studies that have examined the relationship between finance and economic growth in the case of Algeria. In order to be able to control our criticisms, we tried to determine the analysis criteria and the points of similarity between the selected studies. It appears through this study that the relationship between finance and economic growth is analyzed by an econometric method based on mathematical models, which do not always reflect the reality of this relation and remain somewhat superficial, for several reasons mentioned in this study.
Keywords: السياسات المالية -- النمو الاقتصادي -- الاقتصاد القياسي -- الجزائر